Is India a developmental state? - Mukherji, Rahul (The Asian Developmental State, 2016)
This chapter challenges the notion that development can occur only within a classic developmental state. It will briefly describe the conception of a classic developmental state. Thereafter it will argue that the literature is correct to typologize India as a nondevelopmental state. Where the chapter will take issue with notions of the developmental state is in arguing that development is possible in a so-called embedded particularistic state as well (Herring 1999). An “embedded particularistic” state is conceptualized as one where the state lacks the autonomy to pursue its will because of the power of oppositional vested interest that stands in the way of the state.